Self-control and Task Timing Shift Self-efficacy and Influence Willingness to Engage in Effortful Tasks - Ein-Gar, Danit; Steinhart, Yael (Frontiers in Psychology, 2017)
Self-efficacy constitutes a key factor that influences people’s inclination to engage in effortful tasks. In this study, we focus on an interesting interplay between two prominent factors known to influence engagement in effortful tasks: the timing of the task (i.e., whether the task is scheduled to take place in the near or distant future) and individuals’ levels of self-control. Across three studies, we show that these two factors have an interacting effect on self-efficacy. Low self-control (LSC) individuals report higher self-efficacy for distant-future effortful tasks than for near-future tasks, whereas high self-control (HSC) individuals report higher self-efficacy for near-future tasks than for distant future tasks. We further demonstrate how self-efficacy then molds individuals’ willingness to engage in those effortful tasks. Given that a particular task may comprise effortful aspects alongside more enjoyable aspects, we show that the effects we observe emerge with regard to a task whose effortful aspects are salient and that the effects are eliminated when the enjoyable aspects of that same task are highlighted.